Psychopathy and Suicidal Thoughts and Behaviors Revisited: Results From a Statewide Population of Institutionalized Youth - Heirigs, Mark H. (International journal of offender therapy and comparative criminology, 2019)
Suicide is the leading cause of death for incarcerated youth, and up to half of all juveniles in confinement experience suicidal ideation in addition to other psychopathology, including psychopathic personality features. Unfortunately, limited research has investigated the psychopathy-suicidality link among juvenile delinquents and using newer psychopathy measures. Based upon a statewide population of incarcerated juvenile offenders, we found that psychopathy was a significant risk factor for suicidal ideation and lifetime suicide attempts, but the latter relationship was attenuated by lifetime depression diagnosis. In addition, certain affective psychopathic features such as Stress Immunity conferred protection against suicidality, whereas behavioral and lifestyle components including Carefree Nonplanfulness, Blame Externalization, and Rebellious Nonconformity were positively linked to suicidal thoughts among the youth offenders. As these risk factors are routinely screened for in juvenile justice settings, this study's findings have considerable implications to applied practice and prevention among juvenile justice involved youth.